Effects of principals’ leadership styles on teachers’ commitment in Vietnam - Van Dat Tran; Thi Tuong Vy Huynh; Thi A Dong Le (Institute of Advanced Engineering and Science, 2023)
In recent years, styles of transformational and transactional leadership have become an important area of research because of its significant impact on teachers’ outcomes such as commitment, job satisfaction, self-efficacy. However, the relationships between transformational and transactional leadership styles of school principals and teachers’ organizational commitment have been rarely investigated in the educational context in Vietnam. This study aimed to determine how transformational and transactional leadership styles influence the organizational commitment of Vietnamese high school teachers. The study employed two standardized surveys to collect data from 387 teachers at 24 public high schools in the Mekong Delta of Vietnam. The results of correlation coefficient analyses indicated that teachers’ organizational commitment was positively influenced by transformational leadership and negatively influenced by transactional leadership. In addition, the results of multiple regression analyses showed that the organizational commitment of teachers was predicted by all components of both leadership styles of principals. The present study suggested that school leaders might combine both transformational and transactional leadership styles in their leadership practices to improve teachers’ organizational commitment.